"Adenomatous Polyps of the Gallbladder" Adenomas of the Gallbladder. Issue 4 (1991) - Farinon, Attilio Maria; Pacella, Antonio; Cetta, Francesco; Sianesi, Mario
Abstract : The finding of adenomatous polyps of the gallbladder is a rare occurrence and an unusual clinical problem. Among 2, 145 patients who underwent cholecystectomy for gallbladder disease only 9 (0.4 per cent) presented with adenomatous polyps. There were 6 women and 3 men, aged 17 to 70 years. Preoperative ultrasonographic diagnosis was made in only 1 of 7 patients with gallstones, in contrast polypoid lesions within a gallbladder without stones were easily confirmed by both ultrasonography and oral cholecystography in the remaining 2 patients. All polyps were 1.0 cm or less in size and without histologic evidence of malignant change. The clinical significance of this rare condition is discussed, with particular reference to a possible role in development of gallbladder carcinoma. Surgical treatment should be advocated regardless of clinical manifestation when the polyp exceeds 1.0 cm in diameter or rapid growth of the lesion is seen on ultrasonographic follow-up examinations.